Navigating the Growth Imperative: A Consultant’s Perspective on Corporate Growth Strategies - Montalvo , Diego Andres Cevallos; Kraycehte, Leonardo Campelo (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
This article discusses the evolution of sustainable growth, which has gone from being merely a corporate aspiration to a strategic necessity. In a competitive environment where stagnation can mean decline, the continuous pursuit of expansion and value creation is presented as essential for long-term organizational success. From the perspective of strategy and corporate finance consulting, the article highlights that the ability to identify, evaluate, and execute appropriate growth strategies is the determining factor between corporate success and survival. Finally, the study examines the main paths to corporate growth, analyzing their strategic foundations, financial implications, and the contributions of scholars and practitioners in the field.